2010
DOI: 10.1103/physrevb.81.235127
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric transport through strongly correlated quantum dots

Abstract: The thermoelectric properties of strongly correlated quantum dots, described by a single-level Anderson model coupled to conduction-electron leads, is investigated using Wilson's numerical renormalization-group method. We calculate the electronic contribution, K e , to the thermal conductance, the thermopower, S, and the electrical conductance, G, of a quantum dot as a function of both temperature, T, and gate voltage, v g , for strong, intermediate, and weak Coulomb correlations, U, on the dot. For strong cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
301
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(330 citation statements)
references
References 82 publications
(182 reference statements)
29
301
0
Order By: Relevance
“…Subsequently, steady state thermopower curve is nonmonotonic and goes to zero at T =0 eventually. This issue has been confirmed by other sources too 19 . On the other hand, the Kondo resonance is simply nonexistent when the dot is in its initial level since T≫ T K .…”
supporting
confidence: 76%
“…Subsequently, steady state thermopower curve is nonmonotonic and goes to zero at T =0 eventually. This issue has been confirmed by other sources too 19 . On the other hand, the Kondo resonance is simply nonexistent when the dot is in its initial level since T≫ T K .…”
supporting
confidence: 76%
“…Also, recently it has been reported that deviations from the WiedemannFranz law lead to enhancement of ZT in nanocontacts made of two-capped single wall nanotubes [24], quantum dots attached to ferromagnetic leads [18], and strongly correlated quantum dots [25]. The maximization of S 2 GT , discussed earlier, has a direct impact on the dimensionless figure of merit ZT when the phonon contribution to the thermal conductance is ignored…”
mentioning
confidence: 99%
“…[19]. Two-terminal geometries using mesoscopic conductors have been considered, notably using quantum dots [5,20,21,7,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]. In the two-terminal geometry, both temperature and voltage bias are applied to the sample and the thermoelectric response is investigated.…”
Section: Introductionmentioning
confidence: 99%